Complex patterns of chromosome 9 alterations including the p16INK4a locus in Wilms tumours. Issue 1 (16th March 2007) - Natrajan, R; Warren, W; Messahel, B; Reis-Filho, J S; Brundler, M-A; Dome, J S; Grundy, P E; Vujanic, G; Pritchard-Jones, K; Jones, C
Abstract : Background: Previous data implicating genetic and epigenetic events on chromosome 9, including the CDKN2A/2B locus, as molecular predictors of Wilms tumour relapse, have been conflicting. Aims: To clarify this using genome-wide and focused molecular genetic analysis. Methods: Microarray-based comparative genomic hybridisation (aCGH) using genome-wide coverage was applied to 76 favourable histology Wilms tumours. Additional investigation of the 9p21 locus was carried out using loss of heterozygosity (LOH) and fluorescence in situ hybridisation (FISH), as well as immunohistochemistry for CDKN2A/p16 INK4a on a paediatric renal tumour tissue microarray. Results: Approximately half of the tumours were found to show chromosome 9 copy number changes. Those cases which harboured alterations comprised at least four distinct patterns: gain of the entire chromosome, loss of 9p, gain of 9q34, or a more complex combination of gains/losses. None of these tumour groups showed any statistically significant correlation with clinicopathological variables. Deletion mapping of 9p by LOH revealed several regions of overlap, including the CDKN2A/2B locus in 4/34 (11.8%) tumours, which was confirmed to represent hemizygous deletions by FISH. CDKN2A/p16 INK4a protein expression was predominantly negative in Wilms tumours as assessed by immunohistochemistry on a tissue array, reflecting the expression pattern in normal kidney. However, 38/236 (16.1%) non-anaplastic Wilms tumours, 4/9 (44.4%) anaplastic Wilms tumours, 5/7 (71.4%) rhabdoid tumours of the kidney, and 4/10 (40%) clear cell sarcomas of the kidney showed nuclear CDKN2A/p16 INK4a immunoreactivity. Conclusions: These data reveal the complex nature of genetic alterations on chromosome 9 in Wilms tumours, but do not provide evidence for their involvement in or association with treatment failure.